Constructing micropore‐rich nitrogen‐doped carbon for high‐performance supercapacitor and adsorption of carbon dioxide. (14th May 2022) - Sahu, Priya; Mishra, Ranjit; Panigrahy, Sonali; Panda, Prajnashree; Barman, Sudip
Summary: Design of advanced highly porous heteroatom‐doped carbon is desirable for their wide presence in applications like electrochemical energy storage systems, gas adsorption, and separation processes. In this work, porous nitrogen‐doped carbon was developed from ethylenediamine via an in situ self‐doping solvothermal process followed by pyrolysis and KOH activation under high temperature. Micropore‐rich nitrogen‐containing carbon materials were prepared through variation of the KOH/C ratio during activation and their electrochemical performance in alkaline electrolyte as well as CO2 sorption behaviour was evaluated. The porous carbon developed using KOH/C ratio of 2 delivered highest supercapacitor performance in 6 M KOH achieving high specific capacitance of 353 F g −1 with 1 A g −1 of current due to its high pore volume and micropore rich surface. The functionalized carbon delivered CO2 uptake capacities of 4.48 and 3.0 mmol g −1 under temperatures of 273 and 298 K, respectively, at 1 bar pressure with a good CO2 /N2 selectivity of 20.58 and CO2 /CH4 selectivity of 3.83. The existence of nitrogen functional groups, high surface area, and micropore‐rich porous structures may be the essential reasons behind superior electrode performance and CO2 capture capacity of the material. This work hopefully offers a simple development of N‐doped carbon for effective energy storage and CO2 adsorption systems. Abstract : Nitrogen functionalized carbon was developed from ethylenediamine with high surface area of 1202.8 m 2  g −1 . Dependency of structural parameters on change in amount of activating reagent was investigated. Excellent supercapacitor performance with high capacitance of 353 F g −1 with 1 A g −1 of current. High selective adsorption of CO2 over N2 and CH4 was achieved.